Chapter L'eterno confine. L'evoluzione della politica italiana in materia di protezione internazionale e accoglienza sul territorio a seguito della «crisi dei rifugiati» del 2015 - ACOCELLA, Ivana (Studi e saggi, 2021)
The purpose of the article is to investigate the progressive evolution of the Italian policy on international protection and reception system. Following the «refugee crisis» of 2015, various strategies have been tested to «reconfigure» the border and control human mobility, confusing and overlapping the inviolable obligation to protect the right of asylum with security measures aimed at safeguarding public order. The «new mobility control regime» has extended beyond the borders of national states in terms of containment and filtration devices for arriving migrants in search of protection (such as the hotspot approach and border control externalization processes).